The Asymptotic Variance of Extreme Bounds - Magee, Lonnie (The Review of Economics and Statistics, 1990)
An asymptotic approximation to the variances of Leamer's (1983) extreme bounds is given. It can be implemented using standard regression output. Copyright 1990 by MIT Press.